2022
DOI: 10.1371/journal.pone.0272412
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of psychological capital and influence regulation with job satisfaction and job performance

Abstract: Background and aims The individual difference predictors of positive work attitudes and behaviors have been widely investigated in the field of positive organizational scholarship. However, to date, integrating studies linking positive psychological resources, such as Psychological Capital and influence regulation, with positive organizational outcomes are still scarce. Thus, the main aim of the present study was to examine the relationships of Psychological Capital and influence regulation with job satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
1
17
0
1
Order By: Relevance
“…Rebelo et al (2018) found that team psychological capital positively affects team performance. Paliga et al (2022) proved the correlative relationship between psychological capital and job performance at both the individual and team levels (Vanno et al, 2014;Xiaoyun, 2019;Yan et al, 2022). At the same time, Xiaoman et al (2022) show that team-level variables, such as team psychological capital, have a corresponding effect on individual employee-level variables (Okros and Vîrgă, 2022).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…Rebelo et al (2018) found that team psychological capital positively affects team performance. Paliga et al (2022) proved the correlative relationship between psychological capital and job performance at both the individual and team levels (Vanno et al, 2014;Xiaoyun, 2019;Yan et al, 2022). At the same time, Xiaoman et al (2022) show that team-level variables, such as team psychological capital, have a corresponding effect on individual employee-level variables (Okros and Vîrgă, 2022).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 98%
“…There has been research on the impact of individual psychological capital on individual performance and the impact of team psychological capital on team performance. In terms of the impact of individual psychological capital on individual performance, Erxiu et al (2012) used innovation performance as a result variable to explore the impact mechanism of knowledge-based employees’ psychological capital on innovation performance; Yanyun et al (2019) found that employees’ psychological capital in state-owned construction firms positively influenced their job performance; Bogler and Somech (2019) examined the positive correlation between team psychological capital and organizational citizenship behavior, which is an important part of work performance; and Jinfeng et al (2021) found that team psychological capital has a positive impact on individual innovative work behavior, which can promote job performance ( Rebelo et al, 2018 ; Bogler and Somech, 2019 ; Jinfeng et al, 2021 ; Paliga et al, 2022 ). In terms of the impact of team psychological capital on team performance, Liping and Linying (2019) found that team psychological capital has a significant impact on team innovation performance.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Psychology capital merupakan sesuatu yang penting untuk kinerja, baik secara individu maupun kelompok. Menurut penelitian yang dilakukan oleh (Palliga, et al, 2020) bahwa psychology capital secara positif mempengaruhi kepuasan kerja dan hasil kinerja baik secara individu maupun kelompok. Kepuasan kerja tersebut dapat menghasilkan kreativitas individu dalam melakukan pekerjaan sehingga akan berdampak pada hasil kinerja individu atau kelompok.…”
Section: Pendahuluanunclassified
“…A previous study showed that psychological capital can maintain employee work motivation and effectively alleviate psychological stress and negative emotions, as well as job burnout ( 18 ). Employees with higher psychological capital will actively connect with other resources, and promote job satisfaction ( 19 ), and work engagement ( 20 ). However, Martin et al ( 21 ) investigated the intention of nurses to work during the H1N1 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction is usually defined as a positive and pleasant emotional reaction generated by an individual’s overall assessment ( 22 ). Previous studies have shown that job satisfaction has a positive impact on organizational commitment ( 23 ), career identity ( 24 ), job performance ( 19 ), and negative impact on turnover intention ( 22 ). At the same time, job satisfaction was a significant predictor of physical and mental health, as well as subjective well-being ( 25 ).…”
Section: Introductionmentioning
confidence: 99%